2016
DOI: 10.3389/fpsyg.2016.00508
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Anxiety: What Have We Learned in 60 Years?

Abstract: The construct of mathematics anxiety has been an important topic of study at least since the concept of “number anxiety” was introduced by Dreger and Aiken (1957), and has received increasing attention in recent years. This paper focuses on what research has revealed about mathematics anxiety in the last 60 years, and what still remains to be learned. We discuss what mathematics anxiety is; how distinct it is from other forms of anxiety; and how it relates to attitudes to mathematics. We discuss the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
653
5
50

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 583 publications
(738 citation statements)
references
References 148 publications
(209 reference statements)
30
653
5
50
Order By: Relevance
“…We found a significant main effect of MA on PVT Reaction time, which is in line with the suggested negative effect of MA on performance (for review see Dowker et al, 2016). Only reaction time, not accuracy in the maths task was affected by maths anxiety, which again supports the idea that anxiety affects not the effectiveness of performance, but rather processing efficiency of the task (PET, Eysenck & Calvo, 1992).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…We found a significant main effect of MA on PVT Reaction time, which is in line with the suggested negative effect of MA on performance (for review see Dowker et al, 2016). Only reaction time, not accuracy in the maths task was affected by maths anxiety, which again supports the idea that anxiety affects not the effectiveness of performance, but rather processing efficiency of the task (PET, Eysenck & Calvo, 1992).…”
Section: Resultssupporting
confidence: 74%
“…Studies demonstrated that mathematical performance is susceptible to the influence of emotional factors, with mathematics anxiety (MA) playing a particularly important role (Dowker, Sarkar & Looi, 2016). MA has been defined by Richardson and Suinn as "a feeling of tension and anxiety that interferes with the manipulation of numbers and the solving of mathematical problems in a wide variety of ordinary life and academic situations" (Richardson & Suinn, 1972, p. 551).…”
Section: Introductionmentioning
confidence: 99%
“…Appendix B provides a summary and process for addressing math anxiety and the use of bibliotherapy. Math anxiety is a well-documented phenomenon that has affected our society for over sixty years, and not enough is being done to address it in our classrooms or in the way we teach math (Dowker, Sarkar, & Looi, 2016). Bibliotherapy can be an effective means to address the math anxious (See Appendix B).…”
Section: "Everybody Is a Genius But If You Judge A Fish By Its Abilimentioning
confidence: 99%
“…For example, math anxiety is more prevalent in women than men (Dowker et al 2016;Suárez-Pellicioni et al 2016) and it would be instructive to assess, in a larger sample than in the present study, whether the induced math anxiety using our paradigm and the subsequent changes in postural control are different in women and men. Furthermore, identifying the manner in which emotion and balance interact is important in addressing balance problems and falls in older adults.…”
Section: Discussionmentioning
confidence: 97%